The Role of Actors’ Consciense in The Free Health Service Policy Making - Rusdi, Muhammad (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
The research is aimed at describing actors’ conscience (hear / inner-self / sincerity), and to identify other factors that may influence the process of free medical service policy making in the Province of South Sulawesi and the focus of the analysis is about free medical service policy making; how the men behind (we call it as actors) should fight between their conscience and rational thinking the time they argue and propose the policy. By applying qualitative method, data collection of this research is done through an in-depth interview and observation. The results shows that in the policy making process, in general, the actors’ conscience and sincerity only play their role at the latter stage that is when the proposal is being legalised; Other findings say that some factors that could influence their sincerity are the political actors who can control and follow their conscience and give the best in terms of deciding and legalising the policy.